การสังเคราะห์และศึกษาตัวเร่งปฏิกิริยาฐานอินทรีย์สำหรับการเปลี่ยนรูป - วิราพันธ์ ธุมา (จุฬาลงกรณ์มหาวิทยาลัย, 2021)
At present, the world is experiencing many disasters, mainly caused by global warming and climate change caused by an increase in greenhouse gas which is mainly caused by human activities, such as burning fuels, forests, coal and etc. The greenhouse gas the most consists of carbon dioxide (CO2). Therefore, we are interested in synthesizing p(Co-TAPhPc) as a catalyst for reducing CO2 to carbon monoxide (CO) by electropolymerizing Co-TAPhPc on a carbon paper by means of cyclic voltammetry (CV) and examined for its catalytic efficiency for CO2 reduction by the CV and at constant reduction potential of –1.3 V to –1.5 V vs. Ag/AgCl (3 M KCl) by chronoamperometry (CA) in aqueous solutions of 0.5 M KHCO3, 1 M KOH and 30% w/w monoethanolamide (MEA). Product analysis was then performed by gas chromatography (GC) in comparison between carbon paper and carbon paper coated with p(Co-TAPhPc). The results showed that when using the carbon paper, H2 was performed as the only product at maximum Faradaic efficiency (FE) of 67 percent. On the other hand, in the case where the carbon paper coated with p(Co-TAPhPc) was used, CO were obtained as desired with the maximum FE of 35 percent from the CO2 reduction in the 1 M KOH solution at the potential of –1.3 V vs. Ag/AgCl (3 M KCl). Therefore, it can be concluded that p(Co-TAPhPc) had catalytic activity for the CO2 reduction.